KARAKTERISASI SIFAT ELEKTROKIMIA ELEKTRODA KARBON BERBAHAN PELEPAH AREN MENGGUNAKAN LARUTAN ELEKTROLIT Na2SO4 - Decha Apriliany Suwandi; Awitdrus Awitdrus (Komunikasi Fisika Indonesia, 2021)
The electrical energy crisis occurs due to the availability of non-renewable sources of electrical energy. The focus of research is currently developing on how to store electrical energy using biomass energy. This study aims to analyze the electrochemical properties of the palm frond based carbon electrode using electrolyte solution of Na2SO4. Pre-carbonization of palm fronds was carried out using an electric oven with a temperature of 100 °C – 250 °C for 2 hours. Chemical activation using KOH activating agent with a concentration of 0.3 M at 80 °C for 2 hours. Carbonization was carried out at a temperature of 600 °C using an N2 gas environment and followed by a chemical activation process using CO2 gas at a temperature of 850 °C for 2.5 hours. Na2SO4 with a concentration of 0.5 M is used as a solution in the manufacture of supercapacitor cells. The scanning rate is inversely proportional to the specific capacitance value generated. Characterization of electrochemical properties was carried out using the cyclic voltammetry method resulting in a specific capacitance value of 61.71 F/g for a scan rate of 1 mV/s, 57.93 F/g for scan rate of 2 mV/s and 51.37 F/g for scan  rate of 5 mV/s.